Results of a national survey among occupational physicians to estimate the number of workers with active medical devices and their types in the context of managing electromagnetic hazards - Gasparini, Rebecca; Gobba, Fabriziomaria; Bogi, Andrea; Calcagnini, Giovanni; Censi, Federica; Falsaperla, Rosaria; Mattei, Eugenio; Vivarelli, Cecilia; D'Agostino, Simona; Modenese, Alberto (Frontiers in Public Health, 2025)
IntroductionOccupational exposure to electromagnetic fields (EMF) is almost ubiquitous: workers with Active Implantable Medical Devices (AIMD) and Active Wearable Medical Devices (AWMD) are considered at particular risk with respect to occupational risk assessment and health surveillance (HS) procedures, due to possible electromagnetic hazards resulting in interference problems. The identification of these workers is therefore fundamental for prevention purposes. Aim of the study is to provide an estimate of the proportion of workers with AIMD and AWMD, and to list the main types of devices involved.MethodsWe performed an online survey among a sample of Occupational Physicians (OPs) from two Italian Regions.Results132 OPs responded, based their answers on a whole number of more than 200,000 workers visited within HS activities in the previous year. Our results show that the 0.8% of the working population in Italy can be estimated as “particularly at risk” for EMF exposure at the workplaces due to the presence of AIMD or AWMD. The most common AIMD resulted pacemakers and implanted cardioverter defibrillators, involving the 0.24% of the workers. Considering AWMD, the most common resulted hearing aids and hormones/drugs pumps, respectively worn by the 0.25 and the 0.17% of the working population.DiscussionIt should be taken into account that potential interference problems could also occur for levels of exposure to EMFs comparable to those measurable for non-professionally exposed populations. Accordingly, the conditions of increased susceptibility to EMF hazards must be carefully considered for a proper occupational EMF risk prevention: the data presented in this work provide a solid foundation for quantifying the actual impact of workers with AIMD and AWMD in the workplaces, and the main types of devices involved.